Imaging the mantle beneath Iceland using integrated seismological techniques. - Allen, R.M.; Nolet, G.; Morgan, W.J.; Vogfjörd, K.; Bergsson, B.H.; Erlendsson, P.; Foulger, G.R.; Jakobsdóttir, S.; Julian, B.R.; Pritchard, M.J.; Ragnarsson, S.; Stefánsson, R. (Journal of Geophysical Research: Solid Earth, 2002)
Using a combination of body wave and surface wave data sets to reveal the mantle plume and plume head, this study presents a tomographic image of the mantle structure beneath Iceland to 400 km depth. Data comes primarily from the PASSCAL-HOTSPOT deployment of 30 broadband instruments over a period of 2 years, and is supplemented by data from the SIL and ICEMELT networks. Three sets of relative teleseismic body wave arrival times are generated through cross correlation: S and SKS arrivals at 0.03–0.1 Hz, and P and PKIKP arrivals at 0.03–0.1 and 0.8–2.0 Hz. Prior to inversion the crustal portion of the travel time anomalies is removed using the crustal model ICECRTb. This step has a significant effect on the mantle velocity variations imaged down to a depth of ∼250 km. Inversion of relative arrival times only provides information on lateral velocity variations. Surface waves are therefore used to provide absolute velocity information for the uppermost mantle beneath Iceland. The average wave number for the Love wave fundamental mode at 0.020 and 0.024 Hz is measured and used to invert for the average S velocity. Combination of the body wave and surface wave information reveals a predominantly horizontal low-velocity anomaly extending from the Moho down to ∼250 km depth, interpreted as a plume head. Below the plume head a near-cylindrical low-velocity anomaly with a radius of ∼100 km and peak VP and VS anomalies of −2% and −4%, respectively, extends down to the maximum depth of resolution at 400 km. Within the plume head, in the uppermost mantle above the core of the plume, there is a relatively high velocity with a maximum VP and VS anomaly of +2%. This high-velocity anomaly may be the result of the extreme degree of melt extraction necessary to generate the thick (46 km) crust in central Iceland. Comparison of the plume volumetric flux implied by our images, the crustal generation rate, and the degree of melting suggested by rare earth element inversions, suggests that (1) mantle material must be flowing horizontally away from the plume core faster than the overlying lithosphere and (2) the bulk of the plume material does not participate in melting beneath Iceland.